A Stranger in My Own Land: Can a Sojourner Belong to the Household? - Clifton, Bruno (The Biblical Annals, 2023)
Occasionally, the biblical term גר has been taken to refer to a “dependent worker” or “client” based on the thought that household membership can be gained through work provided to the household. Mention of household membership tests the identity of the sojourner in the ancient world as stranger or foreigner; a social category listed with widows and orphans—whose status is also defined by the household— as deserving of protection. Given its centrality as a basic social unit in the ancient Near East, we might expect that purchase in a household would grant a status that dissolves the social distance and attendant consequences (fragility of income, lack of patrimony, object of suspicion) thought to be borne by גרים. In what sense, then, is a “dependent worker” who secures membership in the household a גר ? This article reconsiders how distant a person must be from the society within which he resides to make him a ,גר shifting the semantic emphasis of this term away from origin and towards social integration.